Economic Monitoring Report to the Ad Hoc Liaison Committee - World Bank (Washington, DC, 2016)
The Palestinian economic outlook is worrying: recovering slowly from the recession of 2014, the per capita income growth has almost stagnated and projected growth levels will not support an improvement in living standards. Despite impressive fiscal consolidation efforts over the years, the Palestinian Authority’s (PA) fiscal situation remains fragile with a US$600 million financing gap projected for 2016. The main body of the report is organized in two chapters. Chapter II focuses on recent developments in the real, fiscal and banking sectors while providing a near term outlook that highlights critical challenges facing the Palestinian economy. In view of the need for far-reaching reform, Chapter III presents a stock take of World Bank recommendations to the AHLC meeting over the years, discusses the state of the issues, and suggests a way forward.